Intestinal parasitic infections in HIV/AIDS patients: epidemiological, nutritional and immunological aspects - Amancio, F. A. M. [UNESP]; Pascotto, V. M. [UNESP]; Souza, L. R. [UNESP]; Calvi, Sueli Aparecida [UNESP]; Pereira, Paulo Câmara Marques [UNESP] (Universidade Estadual Paulista (Unesp), Centro de Estudos de Venenos e Animais Peçonhentos (CEVAP), 2012)
This study applied a socioeconomic questionnaire designed to evaluate the frequency of intestinal parasites and characterize epidemiological, nutritional, and immunological variables in 105 HIV/AIDS patients - with and without parasitic infections, attending the Day Hospital in Botucatu, UNESP, from 2007 to 2008. Body mass index was calculated and the following tests performed: parasitological stool examinations; eosinophil, IgE, CD4(+) T and CD8(+) T lymphocyte cell counts; albumin test; viral load measure; and TNF-alpha, IFN-gamma, IL-2, IL-5 and IL-10 cytokine levels. Results were positive for parasitic intestinal infections in 12.4% of individuals. Most patients had good socioeconomic conditions with basic sanitation, urban dwellings, treated water supply and sewage, good nutritional and immunological status and were undergoing HAART. Parasites were found at the following frequencies: Entamoeba - five patients (38.5%), Giardia lamblia-four (30.7%), Blastocystis hominis-three (23.0%), Endolimax nana-two (15.4%), and Ascaris lumbricoides - one (7.7%). There were no significant differences between the two groups for eosinophils, albumin, IgE, CD4(+) T and CD8(+) T lymphocytes, INF-gamma, IL-2, or IL-10. Most patients also showed undetectable viral load levels. Significant differences were found for TNF-alpha and IL-5. These results show the importance of new studies on immunodeficient individuals to increase understanding of such variables.
Keywords: HIV/AIDS; enteroparasites; nutrition; immunology; cytokines